Pharmacotherapy of adolescents in the use of psychoactive substances - Sandra Hernandez Morais de Araújo; Renato Rocha Martins; Flavio Marques Lopes; Nathalie de Lourdes Souza Dewulf (São Paulo State University (UNESP), 2017)
The use of Psychoactive Substances brings problems in several areas of the subject's life such as: health, psychological and social. It´s necessary evaluate the factors involved in drug use and potential drug interactions (PDI) in adolescents using psychoactive substances. It was a Cross-sectional, analytical and quantitative study. The research was carried out at the Center for Psychosocial Care and other drugs for children and adolescents 24h, with adolescents under 18 years of age, using medication. The data were obtained by reviewing the charts and the potential interactions were evaluated through the database Micromedex® and Medscape®. Of the 159 records used, there were 815 PDI. By gravity were 59.4% moderate, 23.8% secondary, 15.7% severe and 1.1% contraindicated. The drugs that presented the most PDI were Chlorpromazine (32.3%) and Diazepam (19.6%). The factors involved in polypharmacy were total PDI and those involved in the occurrence of total PDI were studying and the quantity diagnostic hypotheses. Due to the high PDI index, the relationship with polypharmacy and a high number of diagnostic hypotheses, it is necessary to increase the attention of health professionals regarding the topic and the development of protocols to support decision making.